The comparison of total phenolic and flavonoid between Solanum lycopersium L. and Solanum lycopersium var. cerasiforme / Roslyana Che Din - Che Din, Roslyana (2019)
The objective of this study was to determine total phenolic and flavonoid content from skins, seeds, and pulps of Solanum lycopersium L. and Solanum lycopersium var. cerasiforme. Next, the other objective was to compare the total phenolic and flavonoid from skins, seeds and pulps between Solanum lycopersium L. and Solanum lycopersium var. cerasiforme. In qualitative analysis, there were absence of phenolic and flavonoids in seed but presence in skin and pulp for both samples. In quantitative analysis, total phenolic and flavonoid of Solanum lycopersium L. was higher compared to Solanum lycopersium var. cerasiforme. The total phenolic content in the three part of Solanum lycopersium L. ranged from 40.32 ± 0.12 mg GAE/g to 11.89 ± 0.10 mg GAE/g while Solanum lycopersium var. cerasiforme ranged from 20.69 ± 0.21 mg GAE/g to 5.63 ± 0.15 mg GAE/g. Next, total flavonoids content from skin, pulp and seed of Solanum lycopersium L. ranged from 7.96 ± 0.11 mg GAE/g to 4.20 ± 0.04mg GAE/g while Solanum lycopersium var. cerasiforme ranged from 4.22 ± 0.03mg GAE/g to 2.65 ± 0.03mg GAE/g. Furthermore, the total phenolic and flavonoids of skin and pulp extracts for Solanum lycopersium L. and Solanum lycopersium var. cerasiforme. were significant (p<0.05). Therefore, it is important to consume tomatoes along with their skin in order to attain maximum health benefits. Besides that, a few factors such as optimal condition and use several solvents to maximize the yield of antioxidant should be considered in qualitative analysis.